Chronic pain: the burden of disease and treatment innovations - S. Monti; R. Caporali (PAGEPress Publications, 2015)
Musculoskeletal conditions are the most frequent cause of chronic pain and affect around 1 in 5 adults in Europe. When chronic pain occurs, it becomes disease itself, with substantial clinical, social and economic impact. Effi cacy and tolerability problems are encountered with all therapeutic strategies available to treat musculoskeletal pain. This often limits effective analgesia and patients' long term compliance, with the result that chronic pain is persistently underestimated and undertreated. Tapentadol is a novel, centrally acting analgesic that has been recently commercialized for the treatment of chronic pain. This new molecule, by combining two distinct mechanisms of action, μ-opioid receptor agonism (MOR) and noradrenaline reuptake inhibition (NRI), introduces a new pharmacological class called MOR-NRI. Several studies demonstrated promising results in the management of both nociceptive and neuropathic pain and good tolerability profi le, particularly concerning side effects, compared to traditional opioids. This novel analgesic represents a possible therapeutic option also in the rheumatologic fi eld, particularly in the treatment of osteoarthritis and low back pain.